Acute effects of glossopharyngeal insufflation in people with cervical spinal cord injury. (2nd January 2018) - Nygren-Bonnier, Malin; Schiffer, Tomas A.; Lindholm, Peter
Abstract : Objectives : To evaluate acute effects of glossopharyngeal insufflation (GI) on lung function, airway pressure (Paw ), blood pressure and heart rate (HR) in people with cervical spinal cord injury (CSCI). Design : Case-control design. Setting : Karolinska Institutet, Stockholm, Sweden. Participants : Ten participants with CSCI suffering from lesions between C4 and C8, and ASIA classification of A or B were recruited. Ten healthy particpants familiar with GI were recruited as a reference group. Outcome measures : Spirometry, mean arterial blood pressure (MAP), Paw, and HR were measured in a sitting and a supine position before, during, and after GI. Results : GI in the study group in a sitting position increased total lung capacity (TLC) by 712 ml: P < 0.001, vital capacity (VC) by 587 ml: P < 0.0001, Paw by 13 cm H2 O: P < 0.01, and HR by 10 beats/min: P < 0.001. MAP decreased by 25 mmHg, P < 0.0001. Significant differences were observed between groups comparing baseline with GI. The reference group had a higher increase in; TLC (P < 0.01), VC (P < 0.001), Paw (P < 0.001) and HR (P < 0.05) and a higher decrease in MAP (P < 0.001). With GI in a sitting compared to a supine position, TLC, MAP, HR, Paw remained unchanged in the study group, while residual volume decreased in the supine position (P < 0.01). Conclusion : There was a difference between the groups in the increase in TLC; VC; Paw, HR and in the decrease in MAP with GI, however MAP, HR and Paw responded in similar way in both groups in a sitting as well as a supine position. If performed correctly, the risks of GI resulting in clinically significant hemodynamic changes is low, although syncope may still occur.